Two new species of Valeriana (Valerianaceae) from the center of Mexico - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2003)
Two species of Valeriana of apparently very restricted distribution are described as new. V. emmanuelii, collected in two localities of the southern extreme of the municipality of Morelia, Michoacán, is related to V. retrorsa Fern. and to V. densiflora Benth. V. zamoranensis belongs to the series Ceratophyllae and is only known from the highest part of Cerro Zamorano; it seems to be related to V. zapotecana Barrie and to V. otomiana Barrie.